2018
DOI: 10.1080/00223891.2018.1483378
|View full text |Cite
|
Sign up to set email alerts
|

The Padua Inventory–Washington State University Revision of Obsessions and Compulsions: A Reliability Generalization Meta-Analysis

Abstract: The Padua Inventory-Washington State University Revision (PI-WSUR) is a frequently used test to assess obsessive-compulsive symptoms in screening and clinical contexts. A reliability generalization meta-analysis was carried out to estimate the average reliability of the PI-WSUR scores and its subscales and to search for characteristics of the studies that can explain the heterogeneity among reliability coefficients. A total of 124 independent samples reported some coefficient alpha or test-retest correlation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…The version of the questionnaire was also revealed as a moderator in GHP, P, PF, EF, and CF. As in several previous RG meta‐analyses, the original versions in English of the questionnaires exhibited higher reliability coefficients in comparison to the adaptations (Rubio‐Aparicio et al, 2020; Sánchez‐Meca et al, 2017; Vicent, Rubio‐Aparicio, Sánchez‐Meca, & Gonzálvez, 2019). In addition, in two of the subscales, PF and CF, the use of the questionnaire in North America exhibited higher reliability.…”
Section: Discussionsupporting
confidence: 63%
“…The version of the questionnaire was also revealed as a moderator in GHP, P, PF, EF, and CF. As in several previous RG meta‐analyses, the original versions in English of the questionnaires exhibited higher reliability coefficients in comparison to the adaptations (Rubio‐Aparicio et al, 2020; Sánchez‐Meca et al, 2017; Vicent, Rubio‐Aparicio, Sánchez‐Meca, & Gonzálvez, 2019). In addition, in two of the subscales, PF and CF, the use of the questionnaire in North America exhibited higher reliability.…”
Section: Discussionsupporting
confidence: 63%
“…We assessed OC symptoms using the Padua Inventory-Washington State University Revision (PI-WSUR) (25). We chose the PI-WSUR because of its good test-retest reliability (29) and detailed sub-scales. These subscales enabled us to look at changes in scores over repeated testing and assess sub-scores of interest, such as the contamination obsessions and washing compulsions sub-scores (COWC).…”
Section: Methodsmentioning
confidence: 99%
“…We assessed OC symptoms using the Padua Inventory-Washington State University Revision (PI-WSUR) (25). We chose the PI-WSUR because of its good test-retest reliability (29) is the author/funder, who has granted medRxiv a license to display the preprint in (which was not certified by peer review) preprint…”
Section: Standardized Questionnairesmentioning
confidence: 99%
“…Nonetheless, such additional effort will allow comparisons of sample composition and variability of the studies that reported and induced reliability, in order to determine whether or not the reporting bias scenario is plausible. For instance, Rubio‐Aparicio et al's 72 RG meta‐analysis on the Padua Inventory‐Washington State University Revision of Obsessions and Compulsions (PI‐WSUR) stated in the Methods section: “All study characteristics were not only extracted from studies reporting reliability, but also from those that induced it, with the aim of comparing the characteristics of the studies that both reported and induced reliability” (p. 115). It is important to note that studies that induced reliability are not used in the meta‐analytic integration of the reliability coefficients.…”
Section: The Regema Checklistmentioning
confidence: 99%